Model Updating and Global Eigenvalue Analysis of a Tie-Bolt Rotor Using Zero-Length Contact Elements under Different Preloads - Pu Li; Qi Yuan (Shock and Vibration)
Tie-bolt rotors are composed of several disks fastened by tie bolts where contact properties have a great influence on the modal behavior. In this work, a linear spring-damper element is used to consider the contact stiffness and damping in a tie-bolt rotor. A tie-bolt rotor model is developed using the beam element and the zero-length contact element. Experimental modal testing is performed under different preloads of tie bolts. Model updating is carried out to tune the contact parameters using the Particle Swarm Optimization algorithm. Furthermore, a global eigenvalue evaluation is carried out to demonstrate the impact of the lumped spring-damper element on the modal results. Results show that a larger pretension reduces the influence of contact damping on modal parameters. Compared to antisymmetric modes, symmetric modes are more sensitive to the change of contact damping.